Description Of Cognitive Function In Schizophrenia Patients In The Dadi Regional Special Hospital, South Sulawesi Province - Safira Nurfabirra Dwiyanti; Saidah Syamsuddin; R. Joko Maharto; A. Suheyra Syauki; Ham Fransiskus Susanto (Sean Institute, 2024)
Schizophrenia is a complex disorder and has a major influence on aspects of the sufferer's life with a decrease in cognitive function which is associated with poor functional outcomes. Therefore, this study aims to determine the description of cognitive function in schizophrenia sufferers at the Dadi Regional Special Hospital, South Sulawesi Province.This research was conducted using a cross-sectional approach and descriptive methods from March to April 2024 at RSKD Dadi, South Sulawesi Province. The research subjects, 113 people suffering from schizophrenia, were tested for cognitive function using the Montreal Cognitive Assessment (MoCA) test sheet.The proportion of schizophrenia patients who experience cognitive impairment at RSKD Dadi, South Sulawesi Province is 73%. Of the 73% of schizophrenia patients who experienced cognitive impairment, 53% were male, 41% had elementary school education, 57% did not work, 64% used atypical antipsychotic therapy, and 46% of patients had an illness lasting more than five years